DINAMIKA PERUBAHAN SOSIAL EKONOMI PADA MASYARAKAT KINDANG KABUPATEN BULUKUMBA - Muhammad Yusuf; Andi Agustang (Universitas Negeri Makassar, 2020)
This study aims to describe how the factors and processes of socio-economic change and the impact of socio-economic changes that occur in the Kindang Society of Bulukumba Regency. This type of research uses qualitative research. The technique in determining informants uses snowball sampling techniques, that is, without determining the criteria for informants, so the number of informants will always increase according to the information needs of the Kindang community in Bulukumba Regency. Data collection techniques used were observation, interviews and documentation. Data analysis techniques used by researchers through three stages of work, namely: data reduction, data presentation, and drawing conclusions. Validation of the data used is triangulation. The results of this study indicate that (1) the factors that determine the socio-economic changes of the kindang community are farm produce from clove production which is a familiar commodity with a very high economic value at this time with a high level of productivity in Bulukumba district. (2) The process of socio-economic change in the kindang community occurs between different circumstances and times, where the kindang community experiences an economic crisis in the new order, the formation of the BPPC (Clove Management Agency) which regulates and buys cloves at unreasonable prices, then occurs significant changes during the reform period, with the openness and freedom of the reform period until the price of cloves began to recover and freedom of the reformation period until the price of cloves began to recover and increase so that the welfare of the kindang community could prosper. (3) The impact of socio-economic changes that occur in the kindang community of Bulukumba district. namely improving the economic system of the Kindang community to become a prosperous society and higher social stratification, as well as growing public awareness in the fields of education, politics and culture. Culture in this case encompasses lifestyles and relationships and modern lifestyles so that eroding local cultures such as mutual cooperation have begun to diminish.